TINJAUAN YURIDIS PENGARUH AGAMA KRISTEN PROTESTAN DALAM PECERAIAN (STUDI PUTUSAN No 505/Pdt.G/2020/PN Tng): Legal Review of the Influence of Protestant Christian Religion in Divorce (Study of Decision No. 505/Pdt.G/2020/Pn Tng) - Vica Ariana Febriyanti; Harto (Reformasi Hukum Trisakti, 2025)
Divorce is the end of a marital relationship between a husband and wife which causes the legal and spiritual bond between the two to be broken so that they no longer have the status of a married couple and no longer live their lives in one household. Divorce is not permitted in Protestant Christianity, this causes complexity in the role of Christianity in a marital bond, household relationships, and until divorce occurs. The problem formulation in this study aims to answer the problem regarding the disharmony between the influence of Protestant Christianity in divorce carried out by plaintiffs and defendants who embrace Protestant Christianity with Law Number 1 of 1974. The method used is Normative, and use secondary data supported by primary data in the form of interviews with Pastors. The result and conclusion of this study describe the disharmony between Protestant Christianity in Decision Number 505 / Pdt.g / 2020 / PN Tng, and marriage law in Indonesia. Divorce should be the last resort after serious reconciliation and spiritual guidance efforts have been made, and law enforcement officials need to critically review the decision, taking into account the broad impact, especially on children.